Pemberian Reward and Punishment sebagai Upaya untuk Meningkatkan Kemampuan Sosio Emosional Anak Usia Dini - Eha Julaeha; Muthia Sari; Devi Ayu Kurniawati (Jurnal Syntax Admiration, 2024)
The socio-emotional ability of early childhood is still low, that is the reason behind the researcher to conduct a qualitative research method, a case study at Khalifah 1 Sempu Kindergarten, Serang City. The focus of this research problem is the improvement of early childhood socio-emotional abilities that have not developed properly, one of which is influenced by the understanding of learning about socio-emotional education, therefore the researcher conducted learning using the reward and punishment method as an effort to improve the socio-emotional skills of early childhood at Khalifah 1 Serang Sempu Kindergarten. The purpose of this research is to find out the use of the reward and punishment method in an effort to improve the basic socio-emotional skills of children in Khalifah 1 Serang Sempu Kindergarten. The subjects in this study are 15 Class A early childhood children at Khalifah 1 Serang Sempu Kindergarten for the 2023/2024 school year. The standard of success in this study is that if the child has an improvement in socio-emotional, then this study is declared successful, seen from before being given rewards and punishments and after being given rewards and punishment. Thus, teachers and parents can use the results of this study as a reference in implementing rewards and punishments as an effort to improve children's socio-emotional abilities as needed.